Coping with Terrorism Origins, Escalation, Counterstrategies, and Responses - Reuveny, Rafael; Thompson, William R. (SUNY Press Open Access, 2010)
Terrorism is imprinted on Western society's consciousness. Nearly every week a terrorist attack occurs in the world. The academic world, in attempting to understand terrorism, has often been limited to descriptive work rather than analysis, and has produced surprisingly few mainstream collections on the subject. Coping with Terrorism offers a collection of essays that ask: who are terrorists, what are their goals, who supports them, and how can we combat their tactics? The essays are scholarly, rather than journalistic or ideological, in their approach. As such, they scrutinize a much-discussed and prevalent subject and bring it into the mainstream for international relations.